The Role of the Tourism Office in Increasing Regional Original Income in the Maritime Tourism Sector - Zamzami Zamzami; Budi Hartono; Isnaini Isnaini (Mahesa Research Center, 2023)
formulation of the problem in this study is what is the role of the Tourism Office in increasing regional original income in the marine tourism sector in South Aceh Regency, what are the obstacles to the Tourism Office in increasing Regional Original Revenue in the marine tourism sector in South Aceh Regency. The research method used is a qualitative method, and data analysis techniques use descriptive qualitative. Data collection was obtained from observation, interviews and documentation. The research results show that the development of marine tourism areas in South Aceh District aims to increase local revenue by developing tourism objects by maximizing marine tourism object areas in South Aceh District. The role of the Tourism Office is as a facilitator in terms of increasing the number of tourists and carrying out technical policy studies, coaching, implementing sustainability, developing tourism products, tourism businesses, the obstacles to the Tourism Office in increasing Regional Original Income in the marine tourism sector in South Aceh Regency include: lack of public awareness, lack of quality human resources, limited budget (funds), not yet optimal facilities and infrastructure, lack of partnership programs with the government and private